Comparison of the Risk of Recurrent Clostridioides Difficile Infections Among Patients in 2018 Versus 2013. (17th August 2022) - Guh, Alice Y; Yi, Sarah H; Baggs, James; Winston, Lisa; Parker, Erin; Johnston, Helen; Basiliere, Elizabeth; Olson, Danyel; Fridkin, Scott K; Mehta, Nirja; Wilson, Lucy; Perlmutter, Rebecca; et al.
Abstract: Among persons with an initial Clostridioides difficile infection (CDI) across 10 US sites in 2018 compared with 2013, 18.3% versus 21.1% had ≥1 recurrent CDI (rCDI) within 180 days. We observed a 16% lower adjusted risk of rCDI in 2018 versus 2013 ( P < .0001). Abstract :